2019
DOI: 10.1002/dys.1612
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood educators' knowledge about language and literacy: Associations with practice and children's learning

Abstract: Educators' language and literacy knowledge is considered important for informing classroom practices and thereby supporting children's early language and literacy development. This includes both disciplinary content knowledge (knowledge concerning how oral and written language are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 55 publications
2
38
0
1
Order By: Relevance
“…and three that addressed pedagogical knowledge (e.g., what would you do if a child in your classroom doesn't know a word when reading orally?). 5 The emphasis on phonological awareness in these assessments might explain recent findings by Piasta, Park, Farley, Justice, and O'Connell (2020) and Piasta, Ramirez, Farley, Justice, and Park (2020) that SLK has a statistically significant, linear relation with classroom literacy practices in early childhood classrooms, but the relation to classroom practice and/or student outcomes in the elementary grades, when word-reading/decoding instruction is happening, needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…and three that addressed pedagogical knowledge (e.g., what would you do if a child in your classroom doesn't know a word when reading orally?). 5 The emphasis on phonological awareness in these assessments might explain recent findings by Piasta, Park, Farley, Justice, and O'Connell (2020) and Piasta, Ramirez, Farley, Justice, and Park (2020) that SLK has a statistically significant, linear relation with classroom literacy practices in early childhood classrooms, but the relation to classroom practice and/or student outcomes in the elementary grades, when word-reading/decoding instruction is happening, needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses of the use of language in early education settings have shown that trends have centered on exploring literacy and verbal skill development practices (Markussen-Brown et al, 2017) and have identified the crucial role played by educators' verbal expertise in teaching and learning processes (Justice et al, 2018). In this vein, for example, emphasis has been placed on the impact of educators' language on child language acquisition (Muhinyi & Rowe, 2019), on the specific development of expressive language through play with infants (Cuellar & Farkas, 2018), and/or on specific cognitive skills such as print concept, letter naming and/or phonological awareness (Piasta et al, 2019). In addition, recent studies have examined more specific properties of language and the impact of educator syntax on infants' learning of new vocabulary (Farrow et al, 2020), vocabulary size, syntactical complexity and lexical diversity both of educators and infants (Pizarro et al, 2019), near and clear or far and unclear educator talk (Degotardi et al, 2018), and/or preferences for storytelling and reading versus writing activities and their differential association with verbal syntactic complexity and the acquisition of new vocabulary (Torr, 2020).…”
Section: Evidence-based Characterizations Of Early Childhood Educatorsmentioning
confidence: 99%
“…In a study of 222 early childhood educators, Schachter et al (2016) found that early childhood educators’ disciplinary content knowledge about early language and literacy was associated with the amount of language and literacy support they provided. In a more recent study of 485 PreK teachers, Piasta and colleagues (2019) found that teachers with more disciplinary content knowledge (“knowledge concerning how oral and written language are structured and map to one another”) and knowledge for practice (“knowledge of effective strategies and practices for supporting early language and literacy”) were significantly more likely to engage in more desirable literacy pedagogical practices, and that there were significant positive correlations between teachers’ knowledge and children’s learning of print concepts, letter names, and phonological awareness.…”
Section: Context For the Studymentioning
confidence: 99%